Defrosting Sino-Japanese Relations: What Now? - Jash, Amrita (2017)
The recent commitment to dialogue between Xi Jinping and Shinzo Abe in Hamburg indicates a thaw in China-Japan relations. By favouring a stable relationship, China and Japan are unveiling a ‘new thinking’ to their strained bilateral relationship.